Identification of CD4+ T cells with T follicular helper cell characteristics in the pig. (September 2022) - Hoog, Anna; Villanueva-Hernández, Sonia; Razavi, Mahsa Adib; van Dongen, Katinka; Eder, Thomas; Piney, Lauriane; Chapat, Ludivine; de Luca, Karelle; Grebien, Florian; Mair, Kerstin H.; Gerner, Wilhelm
Abstract: T follicular helper (Tfh) cells provide help to germinal center B cells for affinity maturation, class switch and memory formation. Despite these important functions, this subset has not been studied in detail in pigs due to a lack of species-specific antibodies. We investigated putative Tfh cells from lymphoid tissues and blood of healthy pigs by using cross-reactive antibodies for inducible T-cell costimulator (ICOS) and B-cell lymphoma 6 (Bcl-6). In lymph nodes, we identified a CD4 + T cell population with an ICOS + Bcl-6 + CD8α + phenotype, reminiscent of human and murine germinal center Tfh cells. Within blood-derived CD4 + T cells, sorted ICOS hi CD25 - and ICOS dim CD25 dim cells were able to induce the differentiation of CD21 + IgM +  B cells into Ig-secreting plasmablasts. Compared to naïve CD4 + T cells, these two phenotypes were 3- to 7-fold enriched for cells expressing the Tfh-related transcripts CD28, CD40LG, IL6R and MAF, as identified by single-cell RNA sequencing. These results provide a first characterization of Tfh cells in swine and confirm their ability to provide B-cell help. Highlights: CD4 + T cells with an ICOS + Bcl-6 + CD8α + phenotype form a unique subset in lymph nodes and spleen. Foxp3-expressing ICOS + Bcl-6 + CD4 + T cells have a phenotype that is reminiscent of T follicular regulatory (Tfr) cells. Blood-derived ICOS hi CD25 - and ICOS dim CD25 dim CD4 + T cells can stimulate B cells for antibody production.